Improving Vocational Student’s Accounting Skill Throught Accurate Software Training (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The development of the digital era makes expertise in using technology increasingly necessary for all parties. This digitalization not only occurs in the field of technology, but digitalization occurs in accounting. Vocational students majoring in accounting require training in using accounting software to enhance their skills in accounting digitalization and compete effectively in the workforce. Therefore, this service is carried out so that vocational students can gain expertise in using accurate software. The method used in this service uses mentoring, tutorials, and discussions. The training participants were students of SMK Daan Mogot Jakarta, grades XI and XII. The results of the service showed that students of SMK Daan Mogot Jakarta gained additional skills in the use of accurate accounting software, as seen from the results of the post-test conducted. The results show that 66% of participants passed the certification exam, while the rest did not pass the certification exam. This kind of community service should be carried out regularly for students at vocational schools to improve the skills of those who will work after graduating from school in relation to accounting digitization.